The Effect of Mobile Banking on the Performance of Commercial Banks in Nigeria - Bagudu, Hauwa Daniyan; Khan, Shazida Jan Mohd; Roslan, Abdul Hakim (International Research Journal of Management, IT & Social Sciences, 2017)
Today, commercial banks are confronted with challenges that range from debt crises to the tight competition in the market. Customersâ impatience has increased considerably as they are more knowledgeable than before. Thus, the introduction of mobile services in the banking industry has added to the challenges facing commercial banks as they have to embrace the new technology or lose business. Mobile banking in Nigeria has completely transformed the banking industry and any commercial bank operating in Nigeria can only ignore that fact at its own risk. This study, therefore, aims to investigate the mobile banking effects on Commercial Banks financial performance in Nigeria. Simple random techniques were employed in this study in selecting 22 commercial banks.